2013
DOI: 10.1007/s00403-013-1402-1
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to pay and quality of life in patients with atopic dermatitis

Abstract: Atopic dermatitis (AD) is a frequent and burdensome disease. The objectives of this study were (1) to assess the willingness to pay (WTP) and quality of life (Qol) in AD patients and (2) to compare the results with data on other chronic skin diseases. To collect data, a non-interventional, cross-sectional nationwide postal survey on adult patients with clinically diagnosed AD was performed; socio-demographic data, clinical features/symptoms, WTP and QoL were recorded. WTP was assessed in three different approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
105
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(110 citation statements)
references
References 32 publications
3
105
0
2
Order By: Relevance
“…Previous studies found that sleep disturbances are a risk factor for headaches, as reviewed in previous studies. [12][13][14][15][16][17] Sleep disturbances in patients with eczema have recently been found to be associated with shorter stature 21 and poor health-related quality of life [22][23][24][25][26] in children and poorer overall health, 3 increased fractures and other injuries, 27 and even cardiovascular disease 28 in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that sleep disturbances are a risk factor for headaches, as reviewed in previous studies. [12][13][14][15][16][17] Sleep disturbances in patients with eczema have recently been found to be associated with shorter stature 21 and poor health-related quality of life [22][23][24][25][26] in children and poorer overall health, 3 increased fractures and other injuries, 27 and even cardiovascular disease 28 in adults.…”
Section: Discussionmentioning
confidence: 99%
“…A considerable burden of illness is related to itching chronic skin diseases (11,12), but research on the burden of illness in DH is scant. Previously, a small study (n = 10) showed that DH patients' quality of life did not differ from that of healthy controls at the time of diagnosis, nor after one year of diet (17).…”
Section: Discussionmentioning
confidence: 99%
“…However, dieting is troublesome and compliance difficult (9,10). A substantial burden of illness is also related to a number of itching chronic skin diseases, such as psoriasis and atopic dermatitis (11,12). Although DH is an itching chronic skin disease and an extraintestinal manifestation of coeliac disease, knowledge of its detriments is scarce.…”
Section: Ermatitis Herpetiformis (Dh)mentioning
confidence: 99%
“…Diseaserelated costs also directly affect the patients themselves or their parents. Regarding the behavior of the affected patients from the economic point of view, in particular, patients with AD are characterized by a moderate-to-high willingness to pay, as has been shown in a nationwide German study [7].…”
Section: Why Are Educational Programs For Ad Patients Necessary?mentioning
confidence: 99%
“…Previous studies on patientcentered care focusing on the outpatient situation close to the patients' homes revealed that in this setting, AD patients are mostly insufficiently treated [5] and show more severe limitations of quality of life than those observed in many other chronic skin diseases [6,7]. Insufficient therapy may finally result in a reduction in therapeutic adherence.…”
Section: Why Are Educational Programs For Ad Patients Necessary?mentioning
confidence: 99%